Exosome Loaded in Microneedle Patch Ameliorates Renal Ischemia–Reperfusion Injury in a Mouse Model - Samin Taghavi; Somayeh Keshtkar; Mozhgan Abedanzadeh; Mehrdad Hashemi; Reza Heidari; Samira Sadat Abolmaali; Mahintaj Dara; Mahdokht Hossein Aghdaei; Alireza Sabegh; Negar Azarpira (Stem Cells International)
Conclusion: The use of a microneedle patch containing exosomes is a noninvasive method that enables the release of exosomes in a slow manner. In comparison to exosome injection alone, microneedle patch-exosome treatment offers a longer and more targeted effect that improves renal IRI dysfunction and reduces tissue damage, potentially facilitating the clinical application of exosomes and improving graft survival.